Increase of efficiency cement knitting with the active mineral nanodisperse component - E. V. Voytovich; I. L. Chulkova; E. V. Fomina; A. V. Cherevatova (Вестник СибАДИ, 2017)
In the paper the influence of mineral nanodisperse silica component on reactivity of cement from different producers is studied. Method of introduction of mineral nanodisperse modifier in binding mixture is proposed. Differences of chemical composition of the studied Portland cements are reflected on features of relationship with nanodisperse component. Optimization of content features of nanodisperse component introduction into cement system as well as hardening conditions allow varying its reactivity and promote to intensification of hydration process of clinker minerals, Portlandite fixation into additional C-S-H phases, that leads to strengthening of cement stone structure. Generally, enhancement of efficiency of cement binder is provided with reducing of clinker component up to 20% and improving of strength characteristics of composite up to 20%.